Does COVID-19 change the long-term prospects of latecomer industrialisation? - Tilman Altenburg; Clara Brandi; Anna Pegels; Andreas Stamm; Kasper Vrolijk; Tina Zintl (Deutsches Institut für Entwicklungspolitik (DIE), 2021)
This study explores to what extent the COVID-19 crisis has been a turning point in the industrialisation process and the overall progress of countries towards sustainable development and what this implies for future inclusive and sustainable industrial development policies. The focus of the study is on latecomer economies.In the first part of this study, we show how the prospects for industrialisation are changing. The reasons are manifold, yet the following global megatrends have particularly strong effects: i) digitalisation and automation of production; ii) global economic power shifts, with enormous ramifications for trade flows and global value chains; and iii ) the greening of economies. These trends are interrelated in multiple ways and, in conjunction, shape the direction of structural change. They open up new avenues for inclusive and sustainable latecomer industrialisation - including digital technologies that reduce transaction costs for countries on the periphery that are willing to benefit from trade; the shift of labour-intensive investments from China to other latecomer economies; or the increasing demand for renewable energy and green hydrogen for which many latecomer countries offer excellent conditions. At the same time, digitalisation and increasing environmental standards raise entry barriers to markets, especially for country with weak innovation systems; likewise, automation tends to undermine latecomer countries' traditional advantages in labour-intensive industries. [...]
Keywords: 330; Strukturwandel; Industrialisierung; Coronavirus; Epidemie; Nachhaltige Entwicklung; Wirkungsanalyse; Entwicklungsländer